TIL, USLUBIYAT, NUTQ MADANIYATI VA ADABIY TAHRIR («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article deals with such philological sciences as linguistics, applied linguistics, stylistics, speech culture and literary editing. Their interrelationships with each other in the compilation of various text outputs are discussed.
Keywords: Visual linguistics, category, language system, language units, style, speech, speech communication, form of speech, functional-communicative type, text, functional type, editing, text style.